Dreams, legends, spirituality and miracles: understanding tattoo narratives among contemporary urban men in Java Island, Indonesia. Issue 1 (2nd January 2020) - Handoko, Cons. Tri; Green, Geff
Abstract : This article examines the relationship between dreams and tattooing in the context of the spiritual beliefs in Indonesia. Based on interviews and ethnographic study in the Island of Java, we highlight the importance of dreams, their perceived meanings and significance for male individuals, who have tattooed their bodies with dreamed imagery. Interviews revealed narratives which arise from the tattoos themselves and we relate them to myth, belief and legends familiar to the Javanese; these draw upon religious faith and also more atavistic mystical beliefs. An important source is the Javanese legend of Nyai Roro Kidul, a narrative often seen to legitimise political, royal and magical power. Dream expressions also draw upon popular visual culture as part of a dynamic and ongoing evolution of an embodied discourse of belief. Our case studies reveal that tattooing can be part of the broader mediation of belief in the supernatural where older beliefs can intervene in new domains and contexts for expression.